2020
DOI: 10.1093/toxsci/kfaa073
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation Capacity of Zebrafish (Danio rerio) Early Life Stages: Functionality of the Mercapturic Acid Pathway

Abstract: Zebrafish (Danio rerio) early life stages offer a versatile model system to study the efficacy and safety of drugs or other chemicals with regard to human and environmental health. This is because, aside from the well-characterized genome of zebrafish and the availability of a broad range of experimental and computational research tools, they are exceptionally well suited for high-throughput approaches. Yet, one important pharmacokinetic aspect is thus far only poorly understood in zebrafish embryo and early l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…In a previous study, zebrafish cyp3a65 appear to have bimodal expression 49 , but this was not observed in the set of developmental stages included in our study. For the glutathione transferases, we found substantial variations in expression between different genes, which is also previously shown at the protein expression and enzyme activity level 80 , 81 . Thus, although it has been demonstrated that genes regulated by common transcription factors tend to be located spatially close in the genome sequence and thus facilitate a concerted gene expression 82 , we did not observe such patterns in our datasets.…”
Section: Resultssupporting
confidence: 84%
“…In a previous study, zebrafish cyp3a65 appear to have bimodal expression 49 , but this was not observed in the set of developmental stages included in our study. For the glutathione transferases, we found substantial variations in expression between different genes, which is also previously shown at the protein expression and enzyme activity level 80 , 81 . Thus, although it has been demonstrated that genes regulated by common transcription factors tend to be located spatially close in the genome sequence and thus facilitate a concerted gene expression 82 , we did not observe such patterns in our datasets.…”
Section: Resultssupporting
confidence: 84%
“…This adherence-dependent cell line was originally derived from 24 h post fertilization (hpf) zebrafish embryos via spontaneous immortalization; 20 we selected it under the premise that, based on its origin, it is a suitable representative of zebrafish embryo tissue explored in our prior work. 21 The cells were routinely cultured in Leibovitz L-15 medium supplemented with 10% FBS at 26 ± 2 °C in ambient atmosphere in an incubator in the dark. The cells were subcultured every 5−10 days at a ratio of 1:2 to 1:3 after the formation of a confluent monolayer.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…Subsequently, proteins in each sample were digested with trypsin at 37 °C for 16 h. The samples were desalted using reversed-phase cartridges (Sep-Pak Vac tC18, Waters, United States) and stored at 4 °C until targeted proteomics analysis on the TSQ Vantage (Thermo Scientific, United States), carried out as described in Tierbach et al 27 Analysis of CDNB Biotransformation Products in PAC2 Cells and Exposure Medium. Prior to all sample preparations, cell and medium samples were spiked with 2.5 μL of a reference standard, 2,4dinitrotoluene-S-glutathione (DNT-SG), as described in ref 21. The extraction of CDNB biotransformation products from the cells was performed according to the method established in ref 21, with some modifications.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations